Functional Differentiation of BMP7 Genes in Zebrafish: bmp7a for Dorsal-Ventral Pattern and bmp7b for Melanin Synthesis and Eye Development - Dong, Xiao-Ru; Wan, Shi-Ming; Zhou, Jia-Jia; Nie, Chun-Hong; Chen, Yu-Long; Diao, Jing-Han; Gao, Ze-Xia (Frontiers in Cell and Developmental Biology, 2022)
Bone morphogenetic protein 7 (BMP7) belongs to the transforming growth factor β (TGF-β) family, which not only induces cartilage and bone formation, but also regulates eye development and melanoma tumorigenesis in mammals. In teleosts, BMP7 differentiates into two subtypes, bmp7a and bmp7b, which have clearly differentiated structures. To fully understand the functional differentiation of bmp7a and bmp7b in fish species, we successfully constructed bmp7a and bmp7b gene deletion mutants in zebrafish using CRISPR/Cas9-mediated gene editing technology. Our results showed that bmp7a mutation caused abnormal development of the embryo's dorsal-ventral pattern and led to death; bmp7b mutation induced growth inhibition and increased melanin production in the skin and eye of mutants. Histological analysis revealed that the density of cone cells in the retina of the eyes in bmp7b mutants increased, and behavioral observation showed that the vision and food sensitivity of the mutants were reduced. Transcriptome analysis of the skin and eye tissues showed that the expression changes of wnt7ba and gna14 in bmp7b mutants might promote the increase of melanin. Additionally, the eye transcriptome analysis indicated that changes in the structure of the eyes in bmp7b mutants led to defects in phototransduction, and seven DEGs (rgs9a, rgs9b, rcvrn2, guca1d, grk1b, opn1mw4, and gc2) were identified as key candidate genes that affected the photonic response of the eyes. The study revealed the functional differentiation of bmp7a and bmp7b in teleosts and the first report about the inhibitory effect of bmp7b on melanogenesis may provide useful information for the future research on human melanoma-related diseases.